The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s40560-016-0192-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Critical Care Pain Observation Tool and Behavioral Pain Scale to assess pain in critically ill conscious and unconscious patients: prospective, observational study

Abstract: BackgroundCritically ill patients admitted to intensive care unit (ICU) may suffer from different painful stimuli, but the assessment of pain is difficult because most of them are almost sedated and unable to self-report. Thus, it is important to optimize evaluation of pain in these patients. The main aim of this study was to compare two commonly used scales for pain evaluation: Critical Care Pain Observation Tool (CPOT) and Behavioral Pain Scale (BPS), in both conscious and unconscious patients. Secondary aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 27 publications
1
72
0
3
Order By: Relevance
“…When self‐report is impossible, observational pain scales, including the BPS, have been recommended for clinical use for critically ill adults (Hjermstad et al, ; Gélinas, ; Kotfis et al, ; Severgnini et al, ). The BPS takes into consideration three behavioral dimensions: facial expression, movement/positioning of the upper limbs, and compliance with ventilation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When self‐report is impossible, observational pain scales, including the BPS, have been recommended for clinical use for critically ill adults (Hjermstad et al, ; Gélinas, ; Kotfis et al, ; Severgnini et al, ). The BPS takes into consideration three behavioral dimensions: facial expression, movement/positioning of the upper limbs, and compliance with ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed the results according to the presence of pain. Thus, for the NRS and VAS, a score of >1 (Gélinas, ), and a score of >4 for the BPS, were indicative of the presence of pain (Severgnini et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the sensitivities and specificities of each scale, along with the sensitivity of the combination of the scales, were reported. 8 The BPS was found to be more specific (91.7%) than CPOT (70.8%) but less sensitive (BPS 62.7%, CPOT 76.5%). Interestingly, the combination of BPS and CPOT resulted in better sensitivity (80.4%) than either scale alone, which suggested that perhaps a combination of both scales may improve accuracy in pain detection.…”
mentioning
confidence: 83%
“…As noted in this paper and supported by the literature, pain assessment techniques are imperfect tools and leave room for development of better instruments, especially in the arena of objective assessment of nonverbal individuals. 8 Sadly, many nonverbal patients find communications with nurses to be difficult and unsuccessful. 9 Other areas of concern are the definitions of pain and painful procedures used in this study and similar trials.…”
mentioning
confidence: 99%
“…A CPOT score of > 2 indicates the presence of pain; the sensitivity of the test is 86% while its specificity is 78% for the assessment of severe post-surgical pain [42,43]. The cut-off value suggested for BPS is >5 [44,45].…”
Section: Assessment Of Pain In Critically Ill Patientsmentioning
confidence: 99%